Implementation of Basic Functions in Islamic Education Management to Enhance Learning Quality in Indonesia - Shofa Fauziyah; Mulyawan Sufwandy; Zohaib Hassan Sain (ADARA, 2026)
This study examines the implementation of Islamic Education Management functions in improving the quality of learning at MAN 2 Kabupaten Bandung. The research aims to analyze how planning, organizing, directing, and controlling are applied in daily academic management and how these functions contribute to learning quality. This study is based on original qualitative research using a case study approach. Data were collected through in-depth interviews with the vice principal for curriculum affairs as the main informant, supported by observations and document analysis related to learning management. The findings reveal that learning quality improvement is strongly influenced by participatory planning, collaborative organizing through teacher forums, value-based leadership in directing teachers, and continuous academic supervision oriented toward professional development rather than control. The integration of Islamic values, particularly through structured religious programs, strengthens both academic and spiritual dimensions of learning quality. However, the study also identifies challenges, including high administrative workloads for teachers and frequent curriculum policy changes that limit pedagogical innovation. The study recommends strengthening adaptive management policies, simplifying administrative demands, and enhancing professional collaboration to ensure sustainable improvement in learning quality. These findings contribute to Islamic education management studies by providing empirical evidence of integrated management practices in a madrasah context.